ERGONOMI KOGNITIF PADA BALIHO KAMPANYE PEMILU 2019 DI PERSIMPANGAN STRATEGIS DI KOTA TALUK KUANTAN - Roberta Zulfhi Surya; Gerhana Adjie (Jurnal Teknik Industri Terintegrasi, 2019)
Cognitive ergonomic is the ability of humans to receive information determined by the five senses. The eye is one of the senses that receives the most information. The information obtained is in the form of visual information that can be obtained through displays originating from various sources, then from that information humans take a decision. The current era of reform is that everyone has the same right to be elected as a representative of the people. During the campaign period in all media decorated with advertisements from prospective representatives who fought to gain people's sympathy, one of the most widely used media campaigns was billboards. Billboards are one of the mainstay media in advertising, both products and social service advertisements. Based on this study, it was found that many 2019 election campaign billboards that were made with art considerations were not considerations of readers' comfort which resulted in the non-delivery of information on billboards. Respondents are required to be over 17 years old, have a minimum education of junior high school (high school) in order to know the intentions and goals of billboards for candidates and increase public participation in supporting the success of the 2019 elections. Using 7 questions that have passed the validity test and reliability test , the average rating of respondents is 2.006 in the assessment range 1 to 4, illustrating that most of the billboard campaign designs for the 2019 Election in Taluk Kuantan City have not met ergonomic rules so that the public considers billboards to be less attractive, unsafe and polluting the landscape.